Pulp progenitor cell recruitment is selectively guided by a C5a gradient - Chmilewsky, Fanny; Jeanneau, C.; Laurent, P.; Kirschfink, Michael; About, I. (Journal of dental research, 2013)
It recently became evident that activation of the complement system also contributes to tissue regeneration after infection/injury. The complement-derived fragment C5a induces vascular modifications and attracts cells expressing its receptor (C5aR/CD88) to the site of infection and tissue injury. Besides inflammatory cells, various tissue cells express this receptor. We hypothesized that pulp progenitor cells, being exposed to local complement activation in caries lesions, may respond to C5a via the C5aR. Our work aimed at evaluating the ability of C5a to induce pulp progenitor cell migration that may link complement activation to dentin regeneration. Immunofluorescence analysis of third molar pulp sections showed perivascular localization of the mesenchymal stem cell markers STRO-1 and C5aR. RT-PCR on STRO-1-sorted pulp progenitor cells, co-expressing both STRO-1 and C5aR, revealed high C5aR mRNA levels. Experiments with the C5aR antagonist W54011 revealed that C5a specifically bound to progenitor cells via C5aR, inducing their selective migration toward the C5a gradient. Since we could also demonstrate C5b-9 formation by immunohistochemistry in carious teeth, our findings suggest that, upon local complement activation, C5a induces pulp progenitor cell migration, which may be critical in initiating the regenerative process after dentin/pulp injury.
Gesehen am 14.04.2021